The Effect of Potassium Fertilizer and Chicken Manure on the Growth and Production and Potassium Absorption of Sweet Corn Plants: Zea mays saccharata Sturt - Meylin Kristina Saragih; Lince Romauli Panataria; Efbertias Sitorus; Adventus Leo Gohan D.S (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2025)
The purpose of this study was to determine the effect of Potassium Fertilizer and Chicken Manure on the Growth, Production and Potassium Absorption of Sweet Corn Plants. This study used a Randomized Block Design (RAK) consisting of 2 factors. The first factor is Potassium Fertilizer (K) consisting of 4 levels, namely:K0 = Control (Without fertilizer), K1 = 7.2 g/plot, K2 = 14.4 g/plot, K3 = 21.6 g/plot. The second factor of Chicken Manure Fertilizer (C) consists of 3 treatment levels, namely: C1 = 2160 g/plot, C2 = 2880 g/plot, C3 = 3600 g/plot. The results of this study indicate thatPotassium fertilizer treatment had a significant effect onplant height, weight of cobs with husks per plant, weight of cobs per plot.The treatment of chicken manure has a significant effect onplant height, weight of cobs with husks per plant, and weight of cobs per plot.The interaction between potassium fertilizer and chicken manure had no significant effect on all observation parameters.